THE EFFECT OF THE HANDS ON ACTIVITY LEARNING MODEL ON SCIENCE PROCESS SKILLS IN ELEMENTARY SCHOOL STUDENTS - Purnomo, Heru; Nugraha, Febby Fajar; Rahayu, Galih Dani Septiyan (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
This study aims to determine the effect of the application of the Hands on Activity learning model that is applied in elementary schools (SD) on natural science subjects (IPA), the research method used in this study is quasi-experimental where the research design used was a nonrandomized pretest-posttest control group design, the sample in this study was all third grade students at SDN Cikupa as the experimental group and grade III students at SDN Linggamekar as the control group. the average test for science subjects and the school environment that have similarities. The results of the study were obtained based on the calculation of the average difference in the t test, the P-value (Sig.2-tailed) = 0.343, so the P-value value >ð›¼ which means that H0 cannot be rejected. This can be interpreted that there is no difference in the average final ability of students' science process skills between the experimental and control groups. However, based on the results of the KPS observations that have been tested by U Ngain m, it shows that the U test scores Sig. (2-tailed) = 0.000 then H0 is rejected, this means that there is a significant difference in increasing science process skills between learning using the Hands on Activity model and the conventional model. So, it can be concluded that learning using Hands on Activity on object motion material is influenced by shape and size better than learning using a conventional approach that includes lecture, question-and-answer and experimental methods.Keywords:Â Science learning, science process skills, hands on activity.